1977
DOI: 10.1515/znc-1977-3-404
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molecular Polarization on the Electrochromism of Carotenoids * II. Lutein-Chlorophyll Complexes: The Origin of the Field-Indicating Absorption-Change at 520 nm in the Membranes of Photosynthesis

Abstract: Electrochromic spectra of monolayers of carotenoids (lutein and β-carotene) in contact with monolayers of chlorophylls and of pheophytin a are measured in thin capacitors. A specific inter­ action of one of the OH-groups of lutein with the Mg-atom of chlorophyll is found. The formation of this oriented complex accounts for the fact that a part of the electrochromic absorption-change of lutein depends linearly on the electric field strength, whereas for lutein alone only a smaller, quadratic electrochromism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 0 publications
3
6
0
1
Order By: Relevance
“…As mentioned above, the semiempirical parameters used in these calculations were chosen so as to produce reasonable absorption maxima for carotenoids. The calculated X.., for lutein is 465 nm, which compares well with the experimental value in benzene of 460 nm (5). For neurosporene, comparison is more difficult because the first two vibrational lines are of approximately equal intensity (13).…”
Section: Methodssupporting
confidence: 76%
See 2 more Smart Citations
“…As mentioned above, the semiempirical parameters used in these calculations were chosen so as to produce reasonable absorption maxima for carotenoids. The calculated X.., for lutein is 465 nm, which compares well with the experimental value in benzene of 460 nm (5). For neurosporene, comparison is more difficult because the first two vibrational lines are of approximately equal intensity (13).…”
Section: Methodssupporting
confidence: 76%
“…Molecules with permanent dipoles will of course exhibit a linear response. As expected, in vitro experiments on carotenoids do produce a quadratic response (4,5). Surprisingly, however, the electrochromic response of carotenoids in vivo has been found to be linear in all cases that have been studied.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The strong electrochromic response of these Fx molecules shows that they probably interact with Chl molecules, thereby lending a dipole moment to this molecule. It is also interesting to note that in higher plants the strongest electrochromic response, at around 515 nm, is attributed to lutein/Chl b interactions (Sewe and Reich 1977), suggesting that the long-wavelength absorbing, field-indicating lutein/Chl b pigment pair in the LHCII might be replaced by a similar Fx/Chl c pair in the FCP. (The strong absorption transient of the Fx molecules also indicated that these molecules were oriented in such a way in the thylakoid membrane that they were able to sense the electric field generated by the photosynthetic electron transport.)…”
Section: Resultsmentioning
confidence: 99%
“…They were based on membrane-bound indicators: the electrochromic absorption changes result from lutein-chlorophyll b complexes (40) that are associated with photosystem II. The pH indicator that we used for the internal pH, neutral red, is highly membrane soluble and it intrinsically responds to the surface pH (28 showed that neutral red responded to pH transients in the inner aqueous bulk phase within <100 Aus (28).…”
Section: Discussionmentioning
confidence: 99%